Upregulation of RAC1/PAK1 signalling promotes DNA damage repair in colorectal cancer cells - Barros, Patricia (2020)
Introduction: Colorectal cancer is one of the most prevalent types of cancer worldwide. The GTPase RAC1 and its effector PAK1 have been found overexpressed or hyperactivated in this type of cancers, particularly those with more aggressive and invasive features, which is frequently correlated with resistance to chemotherapeutics and unfavourable clinical prognosis. Previously, we described a new signalling pathway in which activation of RAC1/PAK1 signalling promotes a transcriptional switch between the BCL6 repressor and the STAT5 transcriptional activator at a restricted subset of gene promoters.